Obstacles of Clinical Education and Strategies for the Improvement of Quality of Education in Yasuj University of Medical Sciences - Masood Moghimi; Sima Mohammad Hossini; Zohreh Karimi; MohammadAli Moghimi; Ebrahim Naimi; Somaya Mohammadi; Maryam Behroozi (Golestan University of Medical Sciences, 2014)
Background and Objective: The ideal value of clinical training in personal and professional development, as well as the clinical nursing skills is undeniable. Hence, we aimed at investigating the obstacles of clinical education and strategies for improving the quality of education in Yasuj University of Medical Sciences. Material and Methods: This cross-sectional study was conducted on 108 nursing students who had attended at least one term of practical work in Hospital, 2010. The instrument was a questionnaire, including questions related to demographic characteristics and barriers of clinical skills, whose validity and reliability were approved (R = 0.81). The data was analyzed by SPSS 17. Results: The main obstacles were absence of learning objectives (85.9%), students' failure to maintain discipline (77.8%), lack of adequate training period (66.6%), lack of appropriate communication between students and personnel (62.1%). There was significant difference between male and female students about the importance of training records of instructors. (P